ChemInform Abstract: Selective Deprotection of Benzyl (Bn) Ethers in the Presence of para‐Methoxybenzyl (PMB) Ethers. Issue 28 (July 2015) - Li, Xiaohua; Saleh, Zachary; Egri, Brian; Hourani, Ali; Harding, Luke; Baryal, Kedar N.; Zhu, Jianglong
Abstract An efficient method for chemoselective deprotection of benzyl ethers in the presence of 4‐methoxybenzyl ethers using radical anion reductant lithium 4, 40‐di‐tert‐butylbiphenyl is developed.